Csanád vármegye képviselete az 1847/48. évi utolsó rendi országgyűlésen = Representation of Csanád county at the last Hungarian Diet in 1847/48 - Deák Ádám (Belvedere Meridionale, 2024)
In my study, I present the activity of Csanád county in the Diet on the the deputies instructions, deputy reports, Diet diaries, newspaper reports and literature. Before the last Diet the political life in the counties became liven, and in 1846 the Conservative Party was formed, and in 1847 the Liberal Party was founded. These political movements had a great infulence on the life of Csanád county, three groups were formed (opposition, conservative and center). Many reform programs can be found in the instructions of Csanád county (public taxation, compulsory abolition of serfdom, the abolition of the aviticitas), but the government and the administrative system were not criticized. This proves that the political forces were strongly divided in Csanád county as well. János Rónay and Ferenc Posonyi represented Csanád county in this Diet. During the Diet deliberations, the deputies of Csanád were in favour of reforms, but a conflict arose between them over the case of administrative system. Then, as a result of the revolutions in Paris, Vienna and Pest in 1848, the nobles of Csanád county also supported bourgeois reforms.